Walter Gordon Grant: an archaeological appreciation - Reynolds, Diana M; Ritchie, J N Graham (Proceedings of the Society of Antiquaries of Scotland, 1987)
Grant cleared and consolidated the Broch of Midhowe, Rousay and also examined other Orkney monuments; his chief memorial is the sites he conserved for the national interest.